Database Management System on Raw Material Transaction System Case Study : Sabana Fried Chicken - Septian Rheno Widianto; Stephen Yonathan Sudiro; Irwan Suwandi; Leli Leiliawati (Institute of Computer Science (IOCS), 2020)
Franchise business is a business which has high number of raw material transactions with more than 1300 partners number. Currently, the transaction logging is still done manually which relies on the conventional documents, therefore the overall transaction recording of raw materials in the form of database is really necessary to minimize the errors in terms of the data management. The database management system certainly holds an important role in this case. This system is able to provide assistance in solving problems, to speed up the transaction process of incoming and outgoing goods and also to produce report of raw materials in every distributor or every franchise partner